Occurrence of peat mosses in the Białowieża Forest (NE Poland) and their conservation status - Melosik, Iwona (Biodiversity: Research and Conservation, 2006)
Twenty-two Sphagnum species are reported from the Białowieża Forest in north-eastern Poland. Data on their distribution are based on 243 localities in 122 forest sections. The phytosociological preferences, conservation status, and short description of distribution in Poland of these species are described as well.